A phenomenologic study : Novice nurse experience in facing patients with red triase labels in emergency department (ED) - Eva Marti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Novice nurses category will experience fear, panic, not ready and doubts to interact with patients, families of patients and other more senior nurses. This study aims to describe or explore the burden experience and source of support for novice nurse . The study used a descriptive phenomenology design involving seven participants who were nurse nurses at the emergency department. Data analysis using Braun and Clark thematic analysis. The four themes produced in the study illustrate the experience of novice nurses facing patient with emergent condition in emergency department. Required guidance and mentoring process for novice nurses at the beginning of the working period at the emergency department Keywords: novice nurses , emergency patients